Distinct mast cell subpopulations within and around lymphatic vessels regulate lymph flow and progression of inflammatory-erosive arthritis in TNF-transgenic mice - Peng, Yue; Kenney, H. Mark; de Mesy Bentley, Karen L.; Xing, Lianping; Ritchlin, Christopher T.; Schwarz, Edward M. (Frontiers in Immunology, 2023)
Objective Inflammatory-erosive arthritis is exacerbated by dysfunction of joint-draining popliteal lymphatic vessels (PLVs). Synovial mast cells are known to be pro-inflammatory in rheumatoid arthritis (RA). In other settings they have anti-inflammatory and tissue reparative effects. Herein, we elucidate the role of mast cells on PLV function and inflammatory-erosive arthritis in tumor necrosis factor transgenic (TNF-tg) mice that exhibit defects in PLVs commensurate with disease progression. Methods Whole mount immunofluorescent microscopy, toluidine blue stained histology, scanning electron microscopy, and in silico bioinformatics were performed to phenotype and quantify PLV mast cells. Ankle bone volumes were assessed by μCT, while corresponding histology quantified synovitis and osteoclasts. Near-infrared indocyanine green imaging measured lymphatic clearance as an outcome of PLV draining function. Effects of genetic MC depletion were assessed via comparison of 4.5-month-old WT, TNF-tg, MC deficient KitW-sh/W-sh (cKit-/-), and TNF-tg x cKit-/- mice. Pharmacological inhibition of mast cells was assessed by treating TNF-tg mice with placebo or cromolyn sodium (3.15mg/kg/day) for 3-weeks. Results PLVs are surrounded by MCT+/MCPT1+/MCPT4+ mast cells whose numbers are increased 2.8-fold in TNF-tg mice. The percentage of peri-vascular degranulating mast cells was inversely correlated with ICG clearance. A population of MCT+/MCPT1-/MCPT4- mast cells were embedded within the PLV structure. In silico single-cell RNA-seq (scRNAseq) analyses identified a population of PLV-associated mast cells (marker genes: Mcpt4, Cma1, Cpa3, Tpsb2, Kit, Fcer1a & Gata2) with enhanced TGFβ-related signaling that are phenotypically distinct from known MC subsets in the Mouse Cell Atlas. cKit-/- mice have greater lymphatic defects than TNF-tg mice with exacerbation of lymphatic dysfunction and inflammatory-erosive arthritis in TNF-tg x cKit-/- vs. TNF-Tg mice. Cromolyn sodium therapy stabilized PLV mast cells, increased TNF-induced bone loss, synovitis, and osteoclasts, and decreased ICG clearance. Conclusions Mast cells are required for normal lymphatic function. Genetic ablation and pharmacological inhibition of mast cells exacerbates TNF-induced inflammatory-erosive arthritis with decreased lymphatic clearance. Together, these findings support an inflammatory role of activated/degranulated peri-PLV mast cells during arthritic progression, and a homeostatic role of intra-PLV mast cells, in which loss of the latter dominantly exacerbates arthritis secondary to defects in joint-draining lymphatics, warranting investigation into specific cellular mechanisms.